Sepsis and Immunosenescence in the Elderly Patient: A Review - Martín, Silvia; Pérez, Alba; Aldecoa, Cesar (Frontiers in Medicine, 2017)
Sepsis is a prevalent, serious medical condition with substantial mortality and a significant consumption of healthcare resources. His incidence has increased around 9% annually in general population over the last years and specially in aged patients group. Several risk factors such as comorbidities, preadmission status, malnutrition, frailty and an impared function in the immune system called immunosenescence are involved in the higher predisposition to sepsis in the elderly patients. Inmunosenescence status consists in a functional impairments in both cell-mediated immunity and humoral immune responses and increases not only the risk for develop sepsis but also lead to more severe presentation of infection and maybe is also related with a higher mortality. There is a also a concern about to admit patients in the ICU taking into account that the outcome of elderly patients is poorer compared to younger people. Nevertheless the management of septic elderly patients does not differ substantially from younger people. In addition, the quality of life in septic elderly survivors is also lower than in younger people. But age as alone factor should not be used to determine treatment options because the poorer outcomes is thought to be due to the increased comorbidities and frailty in this group of patients.